Identity and Scene: Alterity and Authenticity in Taxicab Confessions (Imaginations: Journal of Cross-Cultural Image Studies, 2017)
Abstract | This essay examines the visual rhetoric of HBOs reality TV program Taxicab Confessions, New York, New York (2005). Drawing on Burke’s rhetorical understanding of scene and Straw’s approach to scene as a category for the analysis of urban culture, I argue that the taxicab interior and nighttime street images of New York City structure a scene of indeterminacy, intimacy, and “reality,” thus framing the passengers’ self-presentations within a context of “authenticity.” The program’s visual structure locates passengers simultaneously outside of and within social norms and reinforces hegemonic notions of race, gender, and sexuality. Passengers are situated within a scene that positions them as both eccentric and ordinary, while audiences are provided with a symbolic other that works to contain stretched-but-not-broken norms and thus anchor the normality of the viewer.Résumé | Cet article examine la rhétorique visuelle de l’émission de téléréalité d’HBO Taxicab Confessions New York, New York (2005). En m’appuyant sur l’interprétation rhétorique de Burke de la scène et sur l’approche de Straw de la scène en tant que catégorie pour l’analyse de la culture urbaine, je soutiens que l’intérieur du taxi et les images nocturnes des rues de New York créent une scène d’indétermination, d’intimité et de « réalité », cadrant ainsi l’autoreprésentation des passagers dans un contexte d’« authenticité ». La structure visuelle de l’émission permet de situer les passagers tant à l’extérieur qu’à l’intérieur des normes sociales et de renforcer les notions hégémoniques de race, de genre, et de sexualité. Les passagers sont situés dans une scène qui les positionne à la fois comme excentriques et ordinaires, tandis que le public est doté d’une symbolique autre qui travaille à contenir des normes assouplies, mais non enfreintes, enracinant ainsi la normalité du spectateur.